The Relation Between Vitamin D and Gut Microbiota: A Systematic Review (Texas Journal of Multidisciplinary Studies, 2023)
Vitamin D enhances calcium absorption in the gut and ensures proper levels of calcium and phosphate in the bloodstream, which are necessary for normal bone formation and the prevention of hypocalcemic tetany. The gut microbiota is often referred to as an "extra organ" of the body as it performs vital functions for overall well-being. However, emerging research suggests that Vitamin D might impact the gut microbiota as well as anti-inflammatory and immune-modulatory. This systematic review aims to conduct an in-depth analysis of the research on the relationship between vitamin D and gut microbiota, which was published between 2018 and 2023. The most current articles were identified by conducting a comprehensive search on PubMed, Google Scholar, and Web of Science, focusing on articles published between 2018 and 2023. The phrases "vitamin D" and "gut microbiota" (sometimes referred to as "intestinal microbiota" or "microbiome") are the main components of this meta-analysis which presents the findings from twelve separate investigations. The study demonstrated that the structure and functions of the gut microbiota were impacted by vitamin D deficiency. Additionally, a lack of vitamin D resulted in higher levels of Escherichia coli and lower levels of Bifidobacterium, Lactobacillus, and Akkermansia muciniphila. On the other hand, Vitamin D supplements have improved gut flora composition and function. Recent research suggests that vitamin D plays a role in regulating the makeup of the gut microbiota. Recent discoveries have indicated that vitamin D can influence the composition of the microbial communities residing in the gastrointestinal tract. These findings highlight the potential impact of vitamin D on shaping the diversity and balance of the gut microbiota and underscoring the importance of understanding this relationship for overall health and well-being.